PELAKSANAAN PERKAWINAN WALI HAKIM DAN PENYELESAIANNYA DI KANTOR URUSAN AGAMA KECAMATAN GERUNG LOMBOK BARAT - Gunawan, M. Indra (Prodi Ahwal al-Syakhsiyah STAI Darussalam Nganjuk, 2021)
In general, there are still many people who do not or do not understand the factors that cause marriages with guardian judges to be carried out, which results in marriages that must be repeated because there is an error in determining the guardian of marriage, which should be married to a guardian judge but married to a lineage guardian, as well with the wishes of the family of the prospective bride who wants the marriage that has been carried out with the guardian of the judge to be repeated with the guardian of the lineage for reasons of wanting to cover the disgrace in the case of the prospective bride born out of wedlock. Another problem that occurs in the case of marriage with the guardian of the judge is the occurrence of a disharmonious relationship between the bride and groom and the guardian of their lineage who is adal (reluctant) to act as a marriage guardian so that the guardianship is transferred to the judge. This research is presented to reveal the factors that cause marriage with a judge's guardian, and its resolution at the Office of Religious Affairs, Gerung District, West Lombok Regency. The research method used is a qualitative method. The results showed that the factors that led to the implementation of marriages with guardian judges at the KUA of Gerung District from 2013 to 2020, namely: (a) the lineage guardian was outside the region/country; (b) the bride is born out of wedlock; (c) lineage guardians are/reluctant to marry; (d) the bride is a convert and does not have a Muslim lineage guardian; (e) the bride does not have a guardian; (f) guardian nasab mafqūd / missing; and (g) lineage guardians do not meet the requirements because they are insane/insane.